A step towards synthesizing unique UV and visible light excitable AWO4:Eu3+ (A = Ca and Sr) nanophosphors using high energy ball milling method: luminescence differences in going from Ca2+ → Sr2+ - Jena P.; Gupta S.K.; Sudarshan K.; Pathak N.; Singh A.K. (My University, 2025)
Multicolour excitable scheelite type CaWO4:Eu3+ (CEW) and SrWO4:Eu3+ (SEW) nanophosphors were synthesized using high energy ball milling in nano-domain. The synthesized nanophosphors were characterized extensively using Rietveld analysis of X-ray diffraction data, Raman spectroscopy, electron microscopy, energy dispersive spectroscopy and selected area electron diffraction. Differences in optical characteristics of CEW and SEW are probed using time resolved photoluminescence spectroscopy. It was observed that aliovalent doping of Eu3+ in CaWO4 and SrWO4 at divalent Ca/Sr sites leads to formation of cation vacancies as confirmed using positron annihilation lifetime spectroscopy (PALS). PALS also revealed that defect density in SEW is more than CEW which degrades its optical performance by aiding in non-radiative relaxation. The close proximity in ionic radius of Eu3+ and Ca2+ ions leads to better structural homogeneity in case of CEW and less lattice distortion which is reflected in its high emission output and quantum yield. Stark splitting analyses revealed reduction in symmetry around europium ion in SEW as compared to CEW. This is reflected in high asymmetry ratio (EDT/MDT) in case of SEW which directly translates into its high luminescence lifetime. Lifetime spectroscopy also revealed that in both the samples europium ion is localized at two different environments; one closer to defect centre and one is far off. Our study indicates that both these nanophosphors have unique ability to get excited intensely by UV as well as visible light and emit very intense red light which can be explored in phosphor converted white LEDs. Judd–Ofelt analysis indicates better optical performance of CEW as compared to SEW phosphor. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.